Evaluating the performance of a multipart production system using discrete event simulation (DES) - Mat Desa, Wan Laailatul Hanim; Kamaruddin, Shahrul; Mohd Nawawi, Mohd Kamal; Khalid, Ruzelan (IACSIT Press, Singapore, 2013)
This paper aims to demonstrate the ability of Discrete Even Simulation (DES) in detecting bottlenecks.A DES model was developed based on the logic and using data collected from a manufacturing plant in the northern region of Malaysia that specializes in producing aircraft composite parts.The detection of bottlenecks in this study was based on resource utilization and work in process (WIP).From the study, it was found that the DES is capable of analyzing complex and sophisticated system over the more conventional analytical approach.